Grey glass sheet with wide range of visible transmittance and excellent near infrared transmittance

By adjusting the content of iron, manganese, chromium and cobalt in the silicate glass sheet and controlling the ratios R1 and R2, the problem of difficulty in combining the gray appearance and high near-infrared transmissivity of the suction radar system and display equipment in the prior art is solved, and efficient development of silicate glass sheets is achieved.

JP2025514633APending Publication Date: 2025-05-09AGC GLASS EUROPE SA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024558118
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-04-29
Filing Date
2023-04-27
Publication Date
2025-05-09

AI Technical Summary

Technical Problem

The prior art is difficult to develop a silicate glass sheet in self-driving vehicles that combines the gray appearance of the suction radar system (LIDAR) and the display device, while maintaining the range of high near-infrared transmissive mittance and visible transmissive mittance.

Method used

By adjusting the content of iron, manganese, chromium and cobalt in silicate glass sheets, controlling the ratio of Fe2O3, MnO and Cr2O3, ensuring the ratio R1≤1.1 and the ratio R2≥1, achieving a gray appearance and high near-infrared transmissivity, while limiting the content of hexavalent chromium.

Benefits of technology

The gray appearance of silicate glass sheets is achieved, with a wide range of visible light transmission mittance, while maintaining high near-infrared transmission mittance, and is easy to be cut through fiber cone, reducing the toxic content of hexavalent chromium.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025514633000001_ABST
    Figure 2025514633000001_ABST
Patent Text Reader

Abstract

The invention relates to a composition comprising: a. Total iron (Fe 2 O 3 (expressed as 0.02%~0.8%), b. Manganese (expressed as MnO) ≧0.02%; c. Chromium (Cr 2 O 3 (expressed as 0.01%~0.4%), d. Cobalt (expressed as Co) 0.003%~0.03% A silicate type glass sheet having a composition comprising: 2 O 3 * / (49+0.43(Cr 2 O 3 The ratio R1, defined as [Fe *-MnO*)], is less than or equal to 1.1; 2 O 3 * / (34+0.3(Cr 2 O 3 The ratio R2, defined as (R*-MnO*)), is equal to or greater than 1; preferably, it is equal to or greater than 1.2, more preferably, it is equal to or greater than 1.3. 2 O 3 *, MnO* and Cr 2 O 3 *The sum of the total iron, manganese and chromium contents (Fe 2 O 3 +MnO+Cr 2 O 3 ) relative percentage of the total mass of the glass. Such glass sheets provide grey aesthetics, a wide range of visible light transmission while maintaining excellent infrared light transmission. They can be easily cut by filamentary laser cutting for easy and cost-effective production, and provide an acceptable toxicity profile.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a silicate glass sheet having a gray aesthetic that provides a wide range of transmission in the visible region while maintaining excellent transmission in the near infrared region. [Background technology]

[0002] In many applications of cover glass sheets, design and aesthetics are important, in particular the display market and / or the automotive industry are seeking glass sheets with a grey aesthetic.

[0003] Cover glass sheets are generally required for the development of autonomous vehicles that rely on LIDAR systems. Today, the trend and demand from the market is to have their LIDAR systems fully integrated into the vehicle for obvious reasons of aesthetics and damage prevention. LIDAR systems are typically mounted behind one or more inner surfaces of the glazing. The latest developments in LIDAR technology for autonomous vehicles use near-infrared wavelengths, most often around 900, 1050 and 1550 nm. Regular glass (clear, tinted, coated, etc.) used in automobiles is of the soda-lime silicate type, which has the advantage, among other things, of being highly mechanically, chemically and aging resistant, at limited cost.

[0004] Thus, soda-lime silicate glasses have been developed recently to achieve a significantly higher transmittance in the infrared range, ensuring good performance of LIDAR systems at moderate costs; hiding the non-aesthetic elements of said systems from the outside of the car and preserving the level of inherent resistance (mechanical, chemical, ageing) of regular glass: PCT Publication WO 2020 / 057926 A1 describes a silicate type glass composition that contains specific amounts of total iron, manganese and optionally chromium in specific ratios and achieves high infrared transmittance in the range of 1000 nm to 2000 nm, in particular at the wavelengths of interest 1050 nm and 1550 nm, and is therefore valuable within the context of autonomous vehicles, in particular autonomous vehicles that fully integrate a LiDAR system. Another solution has a composition based on iron, chromium and cobalt in specific amounts and ratios, which shows high infrared transmittance at wavelengths of 850 nm, 900 nm and 950 nm that are compatible with other LIDAR systems, while the Cr produced 6+ In PCT Publication Nos. WO 2020 / 200920A1 and WO 2020 / 200912, which describe glass sheets of silicate type that minimize the amount of species, it has been found that these glass compositions, however, achieve very low visible transmittance and therefore cannot be used in all applications, in particular in combination with both LIDAR systems and devices that use visible light transmission, such as display devices and vehicle headlights, and / or do not allow the attainment of cover glass sheets with a grey aesthetic without the expensive addition of another colorant.

[0005] WO 2016 / 202689 proposes a glass composition based on a combination of chromium, cobalt and selenium that achieves a greater transmittance in the infrared than in the visible light combined with a grey aesthetic. However, such a composition requires very large amounts of selenium to obtain the required transmittance in the infrared and neutral color. Such large amounts of selenium should be avoided due to its volatility in molten glass at high temperatures and therefore its processing difficulties in glass production.

[0006] Furthermore, it is well known to use cover glass sheets in displays to achieve the necessary protection of the display device. For example, for the installation of a display device in a car, it is common for the cover glass sheet to be larger than the display device. Typically, the surface of the cover glass sheet above the screen of the display device is textured to improve its optical properties, which may cause unacceptable differences in rendering between the zone of the cover glass sheet that covers the display device and the zone that does not cover the display device, especially when the display is switched off. This difference in appearance is even further increased when the zone of the cover glass sheet that does not cover the display device is smooth and shiny for decorative purposes. Therefore, car designers are looking for cover glass sheets with a grey aesthetic and / or different visible light transmittance to overcome this difference in rendering. Summary of the Invention [Problem to be solved by the invention]

[0007] The current state of the art does not provide a solution for how to formulate a silicate type glass composition for use as a cover glass sheet that combines an attractive grey aesthetic, a wide range of visible light transmittance, while maintaining excellent infrared light transmittance. Furthermore, such glass sheets should be easily cut by filamentation laser cutting for easy and cost-effective production. Finally, such glass sheets must achieve acceptable levels of toxic components, such as hexavalent chromium. [Means for solving the problem]

[0008] The invention relates to a composition comprising: a. Total iron (expressed as Fe2O3) 0.02% to 0.8%; b. Manganese (expressed as MnO) ≧0.02%; c. Chromium (expressed as Cr2O3) 0.01% to 0.4%, d. Cobalt (expressed as Co) 0.003%~0.03% wherein the ratio R1 defined as [Fe2O3* / (49+0.43(Cr2O3*-MnO*))] is less than or equal to 1.1; and the ratio R2 defined as [Fe2O3* / (34+0.3(Cr2O3*-MnO*))] is greater than or equal to 1; preferably greater than or equal to 1.2, more preferably greater than or equal to 1.3. Fe2O3*, MnO* and Cr2O3* are relative percentages with respect to the sum of the total iron, manganese and chromium contents (Fe2O3+MnO+Cr2O3).

[0009] In a preferred embodiment, the composition of the glass sheet of the invention contains Fe, expressed in the form of FeO, less than or equal to 50 ppm (FeO≦50 ppm), preferably less than or equal to 25 ppm (FeO≦25 ppm). 2+ Thus, the composition of the glass sheet of the invention preferably comprises a percentage of FeO relative to the total Fe2O3 of less than 1% by weight of the total composition, preferably less than 0.9% by weight.

[0010] It is an object of the present invention to provide a glass sheet having a gray color. Thus, preferably, the glass sheet has a color index C*=(a*) equal to or less than 3.5 in transmission at 10° SCI, D65 illuminant. 2 +b* 2 ) 1 / 2 where a* and b* are CIELab values ​​measured for a sheet thickness of 4 mm.

[0011] It is a further object of the present invention to provide a glass sheet containing as little toxic hexavalent chromium as possible. Thus, preferably, the composition contains less than or equal to 10 ppm (Cr 6+≦10 ppm), preferably less than or equal to 5 ppm (Cr 6+ Cr(VI) levels (≦5 ppm), and more preferably Cr(VI)-free (Cr 6+ =0 ppm).

[0012] It is another object of the present invention to provide a glass sheet that offers great flexibility in visible light transmittance while maintaining excellent infrared transmittance. Thus, in a first preferred embodiment, the glass sheet has a visible transmittance (TLD4) less than or equal to 20% (TLD4≦20%), preferably greater than or equal to 2% and less than or equal to 20% (2%≦TLD4≦20%). In such a first embodiment, the composition preferably comprises, in a content expressed as a percentage by weight by the total weight of the glass: a. total iron (expressed as Fe2O3) 0.2% to 0.8%, preferably 0.2% to 0.6%; b. Manganese (expressed as MnO) 0.1% to 1%, preferably 0.3% to 0.9%; c. Chromium (expressed as Cr2O3) 0.05% to 0.4%, preferably 0.1% to 0.3%; and d. Cobalt (expressed as Co) 0.01%~0.03% Includes.

[0013] In such a first embodiment, the glass sheet preferably has a wavelength of 850 nm (T 850 ), 950nm(T 950 ) and / or 1050 nm (T 1050 ) at a specific wavelength, the infrared transmittance (T 850-950-1050 ).

[0014] In the second preferred embodiment, the glass sheet has a visible light transmittance (TLD4) greater than 20% and less than or equal to 50% (20% < TLD4 ≤ 50%). In such a second embodiment, the composition of the glass sheet preferably has, as a content expressed as a weight percentage based on the total weight of the glass: a. Total iron (expressed as Fe2O3) 0.1% - 0.3%, preferably 0.12% - 0.28%; b. Manganese (expressed as MnO) 0.15% - 0.6%, preferably 0.2% - 0.55%; c. Chromium (expressed as Cr2O3) 0.04% - 0.15%, preferably 0.045% - 0.12%; and d. Cobalt (expressed as Co) 0.005% - 0.015% including.

[0015] In such a second embodiment, the glass sheet preferably has an infrared transmittance (T 850 ) greater than 84%, preferably greater than 86% at specific wavelengths of 850 nm (T 950 ), 950 nm (T 1050 ) and / or 1050 nm (T 850-950-1050 ).

[0016] In the third preferred embodiment, the glass sheet has a visible light transmittance (TLD4) greater than 50% (50% < TLD4), preferably greater than 50% and less than or equal to 65% (50% < TLD4 ≤ 65%). In such a third embodiment, the composition of the glass sheet preferably has, as a content expressed as a weight percentage based on the total weight of the glass: a. Total iron (expressed as Fe2O3) 0.02% - 0.15%, preferably 0.035% - 0.11%; b. Manganese (expressed as MnO) 0.02% - 0.4%, preferably 0.025% - 0.28%; c. Chromium (expressed as Cr2O3) 0.01% - 0.07%, preferably 0.015% - 0.04%; and d. Cobalt (expressed as Co) 0.003%~0.008% Includes.

[0017] In such a third embodiment, the glass sheet preferably has a wavelength of 850 nm (T 850 ), 950nm(T 950 ) and / or 1050 nm (T 1050 ) at a specific wavelength of more than 88%, preferably more than 90%. 850-950-1050 ). [Brief description of the drawings]

[0018] [Figure 1] Figure 1 illustrates the importance of the ratio R2 within the present invention to obtain the lowest possible concentration of the toxic hexavalent form of chromium. Examples 1-14 from Sets Nos. 1-3 of the present invention were compared with Comparative Examples A, B, E, F and H, which do not meet the R2 ratio requirement. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The invention relates to a composition comprising: a. Total iron (expressed as Fe2O3) 0.02% to 0.8%; b. Manganese (expressed as MnO) ≧0.02%; c. Chromium (expressed as Cr2O3) 0.01% to 0.4%, d. Cobalt (expressed as Co) 0.003%~0.03% A silicate type glass sheet having a composition comprising: The ratio R1, defined as [Fe2O3* / (49+0.43(Cr2O3*-MnO*))], is less than or equal to 1.1; the ratio R2, defined as [Fe2O3* / (34+0.3(Cr2O3*-MnO*))], is greater than or equal to 1. The elements Fe2O3*, MnO* and Cr2O3* are defined as relative percentages with respect to the sum of the total iron, manganese and chromium contents (Fe2O3+MnO+Cr2O3).

[0020] The inventors have surprisingly found that a combination of specific amounts of manganese, chromium and cobalt elements in a medium to high iron glass matrix (200 ppm to 8.000 ppm total iron) makes it possible to arrive at glass sheets that have a grey aesthetic and exhibit a wide range of visible transmittance together with a high infrared transmittance in the region of 850 nm to 1050 nm, while addressing specific ratios R1 and R2. Moreover, it has been found that such glass sheets are simple and cheap to manufacture and can be easily cut by filamentation laser cutting. Finally, such glass compositions have an acceptable toxicity profile, i.e. less than 10 ppm of hexavalent chromium (Cr 6+ ) species concentrations have been found to achieve the required visible and infrared transmittance.

[0021] In order to obtain high infrared transmission in soda-lime silicate glasses which contain a certain amount of iron, which is essentially an impurity in most of the starting materials used, the ferrous iron in the glass, Fe 2+ It is known to reduce the amount of ferrous ions to the maximum extent possible. Indeed, ferrous ions (sometimes expressed as oxide, FeO) in soda-lime silicate glasses absorb in the near infrared due to their broad absorption band centered at 1050 nm. In known chromium-containing low-iron glasses, it is necessary to reduce all Fe to obtain high near infrared transmittance. 2+ Fe 3+ Chromium is added in an amount adapted to oxidize the glass to full iron. Chromium has been known for many years as a typical strong colorant for glass, but increasing the chromium content of the glass further above the threshold required for fully oxidized iron results in the formation of Fe 2 O 3 , as described in WO 2015 / 091106. 2+ The zero amount of Cr in the composition results in a significant decrease in visible transmittance while maintaining a high level of infrared transmittance. 6+ By carefully adjusting the balance of iron, chromium and manganese in the iron-rich matrix, the final glass has a low Fe content.2+ and Cr 6+ Cr (while maintaining high infrared transmittance) 6+ The inventors have surprisingly found that it is possible to dramatically reduce the amount of Fe2O3* in the composition. In fact, it has been found that it is necessary to balance the different components such that the ratio R2, defined as [Fe2O3* / (34+0.3(Cr2O3*-MnO*))], is equal to or greater than 1. Furthermore, it is further necessary to keep the ratio R1, defined as [Fe2O3* / (49+0.43(Cr2O3*-MnO*))], equal to or less than 1.1 to ensure high transmittance in the near infrared.

[0022] Fe2O3*, MnO* and Cr2O3* are defined as the relative percentages of the sum of the total iron, manganese and chromium contents (Fe2O3+MnO+Cr2O3).

[0023] Glass laser cutting has many advantages compared to known traditional cutting methods, such as smooth edges, no chipping and the possibility to easily cut various shapes. Two main laser techniques are widely used to cut glass. The first method involves cutting by bulk heating of the glass sheet with a CO2 laser operating at about 10.6 μm, i.e. at a wavelength where silicate glass strongly absorbs electromagnetic radiation by vibration of the Si-O bonds. The second laser cutting method is filamentation laser cutting, usually performed with a Nd-YAG laser operating at 1064 nm. In this method, the laser beam is focused in the bulk of the glass, generating a plasma that locally modifies the refractive index. This physical change forces the laser beam to focus on the resulting void. By successive self-focusing-defocusing steps, a filament of the void is generated within the glass thickness. This line of fraction is then used to cut the glass sheet. This technique achieves very smooth edges and avoids thermal damage of the glass material. Unlike CO2 laser methods, filamentation laser cutting methods require low absorption at 1064 nm (near infrared) to operate efficiently. Typically, large amounts of Fe 2+ Colored glass, which contains 1064 nm of 1064 nm and therefore strongly absorbs in the near infrared, is difficult to cut by filamentation laser cutting. However, it has been found that glass sheets of the composition of the present invention, despite their gray aesthetic, do not strongly absorb 1064 nm infrared radiation on their surface, thus allowing laser filamentation to be formed throughout the glass sheet. Thus, sheets made of the composition of the present invention can be easily cut by filamentation laser cutting.

[0024] According to the present invention, the composition has a ratio R1, defined as (Fe2O3* / (49+0.43(Cr2O3*-MnO*)), that is equal to or less than 1.1 (R1≦1.1). Such an R1 value is preferably greater than or equal to 1.0. 3+ This allows the complete oxidation of iron to Fe, which absorbs in the near infrared region. 2+According to the present invention, the composition has a ratio R2, defined as Fe2O3* / (34+0.3(Cr2O3*-MnO*), that is equal to or greater than 1 (R2≧1), preferably equal to or greater than 1.2 (R2≧1.2), preferably equal to or greater than 1.3 (R2≧1.3). Such R2 values ​​are consistent with the presence of very low amounts of toxic Cr 6+ Fe2O3*, MnO* and Cr2O3* are the relative percentages of the sum of the total iron, manganese and chromium contents (Fe2O3+MnO+Cr2O3). 。

[0025] According to the invention, the composition comprises the following total iron (expressed in terms of Fe2O3): 0.02% to 0.8% by weight. In this description, when speaking about the total iron content in the glass composition, the terms "total iron" and "Fe2O3" are also used, with total iron being expressed in terms of Fe2O3.

[0026] According to one embodiment of the present invention, the composition preferably contains less than or equal to 50 ppm (FeO≦50 ppm), preferably less than or equal to 25 ppm (FeO≦25 ppm), Fe 2+ The range of contents includes a FeO content (expressed in the form of FeO). This range of contents makes it possible to obtain highly satisfactory properties in terms of infrared transmittance. The amount of FeO is naturally higher for embodiments with a high total iron (Fe2O3), and the amount of acceptable FeO content can preferably be expressed as a percentage of total iron. An acceptable FeO content corresponds when the percentage of FeO relative to total iron is preferably less than 1%, more preferably less than 0.9%.

[0027] Indeed, one objective of the present invention is to provide suitable glass compositions that combine an attractive grey aesthetic with a wide range of visible light transmittance while maintaining excellent infrared light transmittance, making it possible to achieve grey glass sheets that are very opaque with almost no visible light transmittance to grey glass sheets with substantial visible transmittance.

[0028] Thus, in a preferred embodiment, the present invention is formulated to achieve a visible transmittance (TLD4) of less than or equal to 20% (TLD4≦20%), preferably greater than or equal to 2% and less than or equal to 20% (2%≦TLD4≦20%), in a content expressed as a percentage by weight based on the total weight of the glass: a. total iron (expressed as Fe2O3) 0.2% to 0.8%, preferably 0.2% to 0.6%; b. Manganese (expressed as MnO) 0.1% to 1%, preferably 0.3% to 0.9%; c. Chromium (expressed as Cr2O3) 0.05% to 0.4%, preferably 0.1% to 0.3%; and d. Cobalt (expressed as Co) 0.01%~0.03% Includes.

[0029] Glass sheets having the above composition are typically 850 ), 950nm(T 950 ) and / or 1050 nm (T 1050 ) exhibits an infrared transmittance of more than 75%, preferably more than 80%, at a specific wavelength.

[0030] According to this embodiment of the invention, the composition preferably contains less than or equal to 25 ppm (FeO≦25 ppm), Fe 2+ Content (expressed in the form of FeO) is included.

[0031] In another preferred embodiment, the present invention is formulated to achieve a visible light transmittance (TLD4) greater than 20% and less than or equal to 50% (20% < TLD4 ≤ 50%), and in terms of content expressed as a weight percentage based on the total weight of the glass: a. Total iron (expressed as Fe2O3) 0.1% - 0.3%, preferably 0.12% - 0.28%; b. Manganese (expressed as MnO) 0.15% - 0.6%, preferably 0.2% - 0.55%; c. Chromium (expressed as Cr2O3) 0.04% - 0.15%, preferably 0.045% - 0.12%; and d. Cobalt (expressed as Co) 0.005% - 0.015% is included.

[0032] The glass sheet having the above composition typically exhibits an infrared transmittance greater than 84%, preferably greater than 86%, at specific wavelengths of 850 nm (T 850 ), 950 nm (T 950 ), and / or 1050 nm (T 1050 ).

[0033] According to this embodiment of the present invention, the composition preferably contains an Fe 2+ content (expressed in the form of FeO) equal to or less than 25 ppm.

[0034] In another preferred embodiment, the present invention is formulated to achieve a visible light transmittance (TLD4) greater than 50% (50% < TLD4), preferably greater than 50% and less than or equal to 65% (50% < TLD4 ≤ 65%), and in terms of content expressed as a weight percentage based on the total weight of the glass: a. Total iron (expressed as Fe2O3) 0.02% - 0.15%, preferably 0.035% - 0.11%; b. Manganese (expressed as MnO) 0.02% - 0.4%, preferably 0.025% - 0.28%; c. Chromium (expressed as Cr2O3) 0.01% to 0.07%, preferably 0.015% to 0.04%; and d. Cobalt (expressed as Co) 0.003%~0.008% Includes.

[0035] Glass sheets having the above composition are typically 850 ), 950nm(T 950 ) and / or 1050 nm (T 1050 ) exhibits an infrared transmittance of more than 88%, preferably more than 90%, at a specific wavelength.

[0036] According to this embodiment of the invention, the composition preferably contains less than or equal to 15 ppm (FeO≦15 ppm), preferably less than or equal to 10 ppm (FeO≦10 ppm), Fe 2+ Content (expressed in the form of FeO) is included.

[0037] In this description and in the claims, to quantify the visible transmission (also called luminous transmission / transmittance or TL) of a glass sheet, we consider the visible transmission (TLD4) using a D65 illuminant for a sheet thickness of 4 mm at an observation solid angle of 2° (according to standard ISO 9050). Visible transmission (TL) represents the percentage of the radiant flux emitted between wavelengths 380 nm and 780 nm that is transmitted through the glass sheet.

[0038] In the present description and claims, to quantify the infrared transmittance, we consider this transmittance at a specific wavelength of 850 nm, 950 nm or 1050 nm (according to standard ISO 9050) for a sheet thickness of 4 mm at a solid angle of 2°, which corresponds to the specific wavelength of the near IR range transmitted through the glass sheet, i.e. 850 nm (T 850 ), 950nm(T 950 ) or 1050nm(T 1050 ) represents the percentage of the radiant flux emitted by the

[0039] Cr 6+ Hexavalent chromium is generally an undesired species in products, primarily for environmental and health reasons. Hexavalent chromium and its compounds are toxic when inhaled or ingested by the human body. Cr in products 6+ The concentration of Cr is limited by regulations (RoHS Directive (2011 / 65 / EU, (EU)2015 / 863 and ELV Directive (2000 / 53 / EC, (EU)2016 / 774)) 6+ However, this maximum threshold will probably become more restrictive in the near future, and recently, the Cr content in glass products has been increased by 1.5%. 6+ Some customers require that Cr be almost absent. Therefore, according to the present invention, the composition preferably contains ≦10 ppm Cr. 6+ More preferably, the composition comprises Cr 6+ ≦5 ppm, and even more preferably Cr 6+ Not included. Cr in glass 6+ The content can be calculated in a known manner based on the transmission spectrum and the linear absorption coefficients of the cations. These absorption coefficients are based on Bamford data (Bamford, CR (1977). Color generation and control in Glass. Glass Science and Technology, 2, pp224, Elsevier Scientific Publishing Company.).

[0040] According to another embodiment of the invention, the composition of the glass sheet is preferably lithium-free. By "lithium-free", this means that according to the invention, the composition contains ≦0.1% by weight, preferably ≦0.05% by weight, or even ≦0.01% by weight of lithium (expressed as Li2O).

[0041] According to another embodiment of the invention, the composition of the glass sheet is preferably barium-free. By "barium-free", this means that according to the invention, the composition contains ≦0.1% by weight, preferably ≦0.05% by weight, or even ≦0.01% by weight of lithium (expressed as BaO).

[0042] According to yet another embodiment, the composition of the glass sheet comprises NiO in a content of less than 0.1% by weight, preferably less than 0.01% by weight, more preferably less than 0.001% by weight, by weight of the total composition. Preferably, the composition of the glass sheet is free of NiO.

[0043] According to yet another embodiment, the composition of the glass sheet comprises CuO in a content of less than 0.1% by weight, preferably less than 0.01% by weight, more preferably less than 0.002% by weight, by weight of the total composition. Preferably, the composition of the glass sheet is free of CuO.

[0044] This meant that the elements barium, lithium, nickel and / or copper were not intentionally added to the glass batch / raw materials and, if they were present, their content in the composition of the glass sheets only reached the level of impurities inevitably included in production.

[0045] In the present description and claims, to evaluate the color of glass, the CIELab values ​​a* and b* measured for a sheet thickness of 4 mm in transmission at 10° SCI with a D65 illuminant are taken into account. The aesthetics of gray is determined by a C*=(a*) equal to or less than 3.5. 2 +b* 2 ) 1 / 2 It is defined by the color index C*, which is calculated as (C*≦3.5).

[0046] The term "glass" within the meaning of the present invention is understood to mean a completely amorphous material, thus excluding any crystalline, even partially crystalline materials (such as glass-crystalline or glass-ceramic materials). The glass sheets of the present invention can be manufactured starting from a process of melting a batch of glass raw materials in a glass melting furnace / tank, and then forming the resulting molten glass into the desired shape using the float process, drawing process, rolling process or any other known method for manufacturing glass sheets starting from a molten glass composition. In an embodiment of the present invention, the glass sheet is a float glass sheet. The term "float glass sheet" is understood to mean a glass sheet formed by the known float glass method. Other forming / processing processes may follow the manufacturing process. In the present invention, "glass sheet" means a glass article in sheet-like form, such as flat glass, curved glass, bent glass, lens, etc.

[0047] The glass sheets according to the invention may have various sizes, ranging from small (e.g. cover lenses), through medium sizes (e.g. for automotive glazing), to very large sizes (up to "DLF" or "PLF" sizes). Also, the glass sheets according to the invention may have a thickness of 0.1 to 25 mm, depending on the targeted application. Preferably, the glass sheets according to the invention have a thickness of 1 to 8 mm, more preferably 1.5 to 5 mm.

[0048] The silicate glass sheets according to the invention are manufactured from glasses which may belong to various categories. The glasses may thus be glasses of soda-lime silicate, aluminosilicate or borosilicate type etc. Preferably, the composition of the glass sheets comprises, in percentages by weight, expressed relative to the total weight of the glass: SiO255~84% Al2O30-18% B2O30-18% Na2O 0~20% CaO 0~15% MgO 0~12% K2O 0~12% BaO 0-5%.

[0049] In an embodiment, the composition of the glass sheet comprises MgO≧0.1% and preferably MgO≧0.5%.

[0050] More preferably, for reasons of, among other things, low manufacturing costs, the glass composition is a soda-lime-silicate type glass. According to this embodiment, "soda-lime-silicate type glass" means that the composition comprises, in percentages by weight, expressed relative to the total weight of the glass:

[0051] TIFF2025514633000002.tif65170

[0052] In particular, examples of base glass matrices for compositions according to the invention are described in published PCT patent applications WO 2015 / 150207 A1, WO 2015 / 150403 A1, WO 2016 / 091672, WO 2016 / 169823 and WO 2018 / 001965.

[0053] The composition of the glass sheets may contain, in addition to impurities present in particular in the starting materials, small proportions of additives (e.g. agents that aid in the melting or refining of the glass) or components resulting from the melting of the refractories that make up the melting furnace.

[0054] Advantageously, the glass sheet of the present invention may be mechanically or chemically strengthened, it may be bent / curved or deformed in the usual manner (by cold bending, thermoforming, etc.) into any desired configuration, and it may be laminated.

[0055] According to one embodiment of the present invention, the glass sheets of the present invention may be coated with at least one coating. Examples of such coatings are: - thin transparent and electrically conductive layers (i.e. layers based on SnO2:F, SnO2:Sb or ITO (indium tin oxide), ZnO:Al or also ZnO:Ga), - anti-reflection layer, - anti-fingerprint layer or treated to reduce or prevent fingerprint transfer; - Black enamel placement for improved esthetics and bonding, - Silver printed mesh structure for heating function, and / or - an anti-soiling and / or hydrophobic layer.

[0056] The glass sheet of the present invention can be advantageously used as an automobile glazing, in particular as a trim.In such a case, in the context of an autonomous vehicle, the LIDAR system can be fully integrated in the vehicle (thereby ensuring aesthetics and preventing damage to the system) and is mounted behind the inner surface of said glazing.The present invention therefore also relates to the use of the glass sheet of the present invention as an automobile glazing, preferably as a trim element; or as a cover lens for a LIDAR sensor.

[0057] Although the background of the present invention has been described with respect to the specific application of vehicle-integrated LIDAR systems, the glass sheet of the present invention may also be advantageously used in any other technology requiring suitable light transmission and / or grey aesthetics, together with very good performance in the near-IR range, especially from 850 nm to 1050 nm. For example, it may be valuable in "Planar Scattering Detection" (PSD) or "Frustrated Total Internal Reflection" (FTIR) optical techniques for detecting the position of one or more objects (e.g., a finger or stylus) on the surface of said sheet, which, due to its rather intense color to grey, may partially or completely hide objects / components found behind / below it.

[0058] Other uses of the glass sheet of the invention are: -Decorative interior panels for the car a decorative panel, which is placed in front of / around the radiant heating element and which hides (partially or completely) the less aesthetic side of the heating element but allows the infrared radiation to pass through, thus allowing a good output from said heating element; - architectural or decorative spandrel glass, - substitutes for commonly used expensive special glass for cooking plates (vitroceram or borofloe or even pyrex), - portable computer pointing devices (commonly known as "touch pads"), which may use technology requiring infrared light, in which case the glass sheet is preferably very dark, and in fact even opaque, thus hiding the electronic components placed underneath; - as a front element of furniture and in particular a front element of furniture intended to be equipped with remotely controllable electric / electronic appliances, making the less aesthetic aspects of such appliances invisible but allowing the signal emitted by the remote control to pass through. This is because the majority of domestic electric / electronic appliances (televisions, hi-fi, DVD players, games consoles, etc.) are remotely controllable using housings that emit signals in the near infrared range. However, this remote control system presents in particular two disadvantages: (i) the signal is often disturbed by the presence of secondary radiation in the visible range (sunlight, lighting), making it less sensitive, and (ii) it requires that the electrical appliances are reachable by the IR signal of the remote control, and therefore these cannot be made invisible in the furniture product, even if the demand is also moving in this direction for aesthetic reasons.

[0059] Throughout this specification, when ranges are given, the end values ​​are included unless expressly indicated otherwise. Furthermore, all integer values ​​and subdomain values ​​of numerical ranges are expressly included as if expressly written. Also, throughout this specification, content values ​​are in weight percentage units (i.e., ppm units) expressed relative to the total weight of the glass (also referred to as weight %) unless expressly indicated otherwise. Furthermore, when a glass composition is given, this relates to the bulk composition of the glass.

[0060] Those skilled in the art understand that the present invention is in no way limited to the above-mentioned preferred embodiments. On the contrary, many modifications and variations are possible within the scope of the appended claims. It is further noted that the present invention relates to all possible combinations of the features and preferred features described herein and recited in the claims.

[0061] The following examples are provided for illustrative purposes and are not intended to limit the scope of the present invention. EXAMPLES

[0062] Different glass sheets / samples according to the invention and not according to the invention (for comparison) were prepared with varying amounts of total iron, manganese, chromium and cobalt in three sets of examples.

[0063] For the preparation of the glass samples, the starting materials were mixed in powder form and placed in a crucible for melting according to the same base composition specified in the table below, which was added to the starting materials containing variable amounts of total iron, manganese, cobalt and chromium as a function of the content targeted for the final composition (it should be noted that iron is already present, at least in part, as an impurity in the starting materials of the base composition).

[0064] TIFF2025514633000003.tif73170

[0065] The optical properties of each sample molded and processed in the form of a sheet were determined on a Perkin Elmer Lambda 950 spectrophotometer equipped with an integrating sphere having a diameter of 150 mm, in particular: - For a thickness of 4 mm, a specific wavelength, i.e. 850 nm (T 850 ), 950nm(T 950 ), 1050nm(T 1050 ) to determine the near-infrared transmittance. The light transmittance TLD4 was also determined according to the ISO 9050 standard (using a D65 light source) for a thickness of 4 mm at an observation solid angle of 2° and for the wavelength range between 380 and 780 nm.

[0066] Set Number 1 Examples 1 to 3 correspond to glass sheets according to the invention exhibiting a TLD4 between 3% and 20%. Comparative Examples A and B correspond to glasses having the required components but not achieving a ratio R2 defined as [Fe2O3* / (34+0.3(Cr2O3*-MnO*))] equal to or greater than 1. Comparative Examples C and D correspond to glasses having iron, manganese, chromium, cobalt and selenium. They do not achieve a ratio R1 equal to or less than 1.1 [Fe2O3* / (49+0.43(Cr2O3*-MnO*))]. All comparative examples show similar values ​​of TLD4 compared to Examples 1 to 3.

[0067] Each of Examples 1 to 3 according to the present invention is - achieving a grey aesthetic as indicated by a C* of ≦3.5; -3%~20%, especially TLD4 visible transmittance of less than 5%, reaching substantial opacity; -850nm(T 850 ), 950nm(T 950 ) and / or 1050 nm (T 1050 ) maintaining its near infrared transmittance of more than 75%, or even more than 80%, at a particular wavelength; -Very low amount of hexavalent chromium Cr 6+ have It was optimized as follows.

[0068] Table 1 shows the optical properties, amounts of iron, manganese, chromium and cobalt, FeO and Cr for Examples 1 to 3 and Comparative Examples A to D. 6+ These amounts, as well as their determined ratios R1 and R2, are presented.

[0069] TIFF2025514633000004.tif241170

[0070] Table 1 shows that the presence of total iron, cobalt, manganese and chromium in the content according to the invention makes it possible to obtain grey glass sheets (C* below 3.5) with low to very low visible transmittance (18.5% - 3%) and high near infrared transmittance (75.5% - 88.4%), while keeping in mind the ratio conditions R1 and R2. Indeed, chromium and manganese are present in small amounts compared to iron, since R1 ≦ 1.1, to achieve such an acceptable near infrared transmittance for TLD4. The low chromium and manganese contents also satisfy the ratio R2 ≧ 1, and therefore according to the invention, Cr 6+ is hardly formed.

[0071] Comparative Examples A and B satisfy the ratio R1≦1.1 and show high near-infrared transmittance. However, these comparative examples do not satisfy the ratio R2 and have a higher level of Cr. 6+ Comparative Examples C and D further illustrate the importance of the ratios R1 and R2: these glasses have a fair gray color, a rather opaque aesthetic due to their low TL, and a Cr 6+ Even if non-containment is achieved, their transmittance at near infrared wavelengths is extremely low (2.5%-15.1%) with the ratio R1 being well above 1.1.

[0072] Set Number 2 Examples 4 to 10 correspond to glass sheets according to the invention exhibiting a TLD4>20% and ≦50%.

[0073] Comparative Examples E and F correspond to glasses that have the required components but do not achieve a ratio R2 defined as [Fe2O3* / (34 + 0.3(Cr2O3* - MnO*))] equal to or greater than 1. Comparative Example G corresponds to a glass having iron, manganese, chromium, cobalt, and selenium. This comparative example does not achieve a ratio R1 of [Fe2O3* / (49 + 0.43(Cr2O3* - MnO*))] equal to or less than 1.1. All comparative examples exhibit a TLD4 of similar value compared to Examples 4 - 10.

[0074] Each of Examples 4 - 10 according to the present invention - Achieves a gray aesthetic as indicated by C* ≤ 3.5; - Achieves a visible transmittance TLD4 of >20% to ≤50%; at 850 nm (T 850 ), 950 nm (T 950 ) and / or 1050 nm (T 1050 ), maintains a near-infrared transmittance of >84%, preferably >86% at specific wavelengths; - Is optimized to have a very low Cr 6+ content as such.

[0075] Table 2 presents the optical properties, their respective amounts of iron, manganese, chromium, and cobalt, their amounts of FeO and Cr 6+ , and their determined ratios R1 and R2 for Examples 4 - 10 and Comparative Examples E - G.

[0076] TIFF2025514633000005.tif209170

[0077] Table 2 shows that the presence of total iron, manganese, chromium, and cobalt in the content according to the present invention enables the obtaining of a gray glass sheet having a medium visible transmittance (20% < TLD4 ≤ 50%) and a high near-infrared transmittance (84.6% - 90.2%) at 1050 nm while taking into account the ratio conditions R1 and R2.

[0078] Comparative Examples E and F illustrate that even if these glasses contain an appropriate amount of iron, manganese, chromium, and cobalt, which have a gray color and a high transmittance in the range of 850 to 1050 nm, they cannot achieve a balance of such components in an appropriate ratio R2, which is represented by a very much higher level of the hexavalent form of chromium (22 and 30 ppm compared to Examples 4 and 10 (≤1 ppm)). Comparative Example G illustrates that even if this glass achieves an appropriate TL, its transmittance at near-infrared wavelengths is extremely low (12.4% to 18.5%) due to its ratio R1, which is considerably higher than 1.1.

[0079] Set number 3 Examples 11 to 14 correspond to glass sheets according to the invention that all exhibit a TLD4 greater than 50%, preferably greater than 50% and less than or equal to 65% (50% < TLD4 ≤ 65%). Comparative Example H corresponds to a glass composition that has the required components but does not achieve a ratio R2 defined as [Fe2O3* / (34 + 0.3(Cr2O3* - MnO*))] equal to or greater than 1. Comparative Example J corresponds to a glass having iron, manganese, chromium, cobalt, and selenium. This comparative example does not achieve a ratio R1 of [Fe2O3* / (49 + 0.43(Cr2O3* - MnO*))] equal to or less than 1.1. All comparative examples exhibit similar values of TLD4 compared to Examples 11 to 14.

[0080] Each of Examples 11 to 14 according to the invention - achieves a gray aesthetic as indicated by C* ≤ 3.5; - achieves a visible transmittance TLD4, 50% < TLD4 ≤ 65%; at specific wavelengths of 850 nm (T 850 ), 950 nm (T 950 ), and / or 1050 nm (T 1050 ), maintains its near-infrared transmittance greater than 88%, preferably greater than 90%; - has a very low Cr 6+ content and is thus optimized.

[0081] Table 3 shows the optical properties, their respective amounts of iron, manganese, chromium and cobalt, FeO and Cr for Examples 11 to 14 and Comparative Examples H and J. 6+ and their determined ratios R1 and R2 are presented.

[0082] TIFF2025514633000006.tif239170

[0083] Table 3 shows the presence of total iron, cobalt, manganese and chromium in the composition according to the invention, while noting the ratio conditions R1 and R2, and very low amounts of Cr 6+ It is shown that it is possible to obtain a gray glass sheet having a medium to high visible transmittance (51% to 65%) and a high near-infrared transmittance (88.7% to 91.3%) while maintaining the above properties.

[0084] Comparative Example H illustrates that even if the glass contains the proper amounts of iron, manganese, chromium and cobalt, but fails to balance such components in the proper ratio R2, such a composition can achieve the proper gray aesthetics and maintains very satisfactory near infrared transmittance, but exhibits much higher levels of the hexavalent form of chromium. Approximately 10% of the chromium introduced into the glass composition remains in the toxic hexavalent form (Cr 6+ / Crtot=8.9%).

[0085] Comparative Example J illustrates that by lowering the chromium content, the hexavalent form of chromium is avoided, but the R1 ratio cannot be met, so that its transmittance at near infrared wavelengths is rather poor (47.8%-54.5%) for a glass with intermediate optical transmittance.

Claims

1. In contents expressed as percentages by weight based on the total weight of glass: a. Total iron (Fe 2 O 3 0.02% to 0.8%, b. Manganese (expressed as MnO) ≧0.02%; c. Chromium (Cr 2 O 3 0.01% to 0.4%, d. Cobalt (expressed as Co) 0.003% to 0.03% A silicate type glass sheet having a composition comprising: [Fe 2 O 3 * / (49+0.43(Cr 2 O 3 The ratio R1, defined as [Fe*-MnO*)], is equal to or less than 1.1; 2 O 3 * / (34+0.3(Cr 2 O 3 The ratio R2, defined as [R*-MnO*)], is equal to or greater than 1; 2 O 3 *, MnO* and Cr 2 O 3 *The total content of iron, manganese and chromium (Fe 2 O 3 + MnO + Cr 2 O 3 ) the glass sheet.

2. [Fe 2 O 3 * / (34+0.3(Cr 2 O 3 2. The glass sheet according to claim 1 , wherein the ratio R2, defined as [MnO*−MnO*)] is equal to or greater than 1.2, preferably equal to or greater than 1.

3.

3. The composition contains FeO, expressed in the form of FeO, less than or equal to 50 ppm (FeO≦50 ppm), preferably less than or equal to 25 ppm (FeO≦25 ppm). 2+ The glass sheet according to claim 1 or 2, comprising:

4. The composition preferably contains less than 1% by weight of the total composition, and more preferably less than 0.9% by weight of Fe. 2 O 3 The glass sheet according to any one of claims 1 to 3, comprising a percentage of FeO relative to

5. The composition has a color index C*=(a*) equal to or less than 3.5 in transmission at 10° SCI, D65 illuminant. 2 +b* 2 ) 1/2 5. The glass sheet according to any one of claims 1 to 4, having a refractive index of 0.1 to 0.5, wherein a* and b* are CIELab values ​​measured for a sheet thickness of 4 mm.

6. Equal to or less than 10 ppm (Cr 6+ ≦10 ppm), preferably equal to or less than 5 ppm (Cr 6+ ≦5 ppm) hexavalent chromium, and more preferably, hexavalent chromium-free (Cr 6+ The glass sheet according to any one of claims 1 to 5, wherein the glass has a refractive index of 0 ppm or less.

7. 7. The glass sheet according to any one of claims 1 to 6, having a visible transmission (TLD4) less than or equal to 20% (TLD4≦20%), preferably greater than or equal to 2% and less than or equal to 20% (2%≦TLD4≦20%), measured with a D65 illuminant according to standard ISO 9050 at a solid angle of observation of 2° for a sheet thickness of 4 mm.

8. The composition, in a content expressed as a percentage by weight based on the total weight of glass, comprises: a. Total iron (Fe 2 O 3 0.2% to 0.8%, preferably 0.2% to 0.6%; b. Manganese (expressed as MnO) 0.1% to 1%, preferably 0.3% to 0.9%; c. Chromium (Cr 2 O 3 0.05% to 0.4%, preferably 0.1% to 0.3%; and d. Cobalt (expressed as Co) 0.01% to 0.03% The glass sheet of claim 7 comprising:

9. 850 nm (T 850 ), 950 nm (T 950 ) and / or 1050 nm (T 1050 ) at a specific wavelength of more than 75%, preferably more than 80% infrared transmittance (T 850-950-1050 9. The glass sheet of claim 7 or 8, having a thickness of 100 nm to 150 nm.

10. 7. The glass sheet according to any one of claims 1 to 6, having a visible transmission (TLD4) greater than 20% and less than or equal to 50% (20%<TLD4≦50%), measured with a D65 illuminant for a sheet thickness of 4 mm at a solid observation angle of 2° according to standard ISO 9050.

11. The composition, in a content expressed as a percentage by weight based on the total weight of glass, comprises: a. Total iron (Fe 2 O 3 0.1% to 0.3%, preferably 0.12% to 0.28%; b. Manganese (expressed as MnO) 0.15% to 0.6%, preferably 0.2% to 0.55%; c. Chromium (Cr 2 O 3 0.04% to 0.15%, preferably 0.045% to 0.12%; and d. Cobalt (expressed as Co) 0.005% to 0.015% The glass sheet of claim 10 comprising:

12. 850 nm (T 850 ), 950 nm (T 950 ) and / or 1050 nm (T 1050 ) at a specific wavelength of more than 84%, preferably more than 86% infrared transmittance (T 850-950-1050 12. The glass sheet of claim 10 or 11, having a thickness of 100 nm to 150 nm.

13. 7. The glass sheet according to any one of claims 1 to 6, having a visible transmission (TLD4) of more than 50% (50%<TLD4), preferably from more than 50% to less than or equal to 65% (50%<TLD4≦65%), measured with a D65 illuminant for a sheet thickness of 4 mm at a solid observation angle of 2° according to standard ISO 9050.

14. The composition, in a content expressed as a percentage by weight based on the total weight of glass, comprises: a. Total iron (Fe 2 O 3 0.02% to 0.15%, preferably 0.035% to 0.11%; b. Manganese (expressed as MnO) 0.02% to 0.4%, preferably 0.025% to 0.28%; c. Chromium (Cr 2 O 3 0.01% to 0.07%, preferably 0.015% to 0.04%; and d. Cobalt (expressed as Co) 0.003% to 0.008% The glass sheet of claim 13 comprising:

15. 850 nm (T 850 ), 950 nm (T 950 ) and / or 1050 nm (T 1050 ) at a specific wavelength of more than 88%, preferably more than 90% infrared transmittance (T 850-950-1050 15. The glass sheet of claim 13 or 14, having a thickness of 100 nm.